Study of LaxNiOy and LaxNiOy/MgAl2O4 catalysts in dry reforming of methane. (March 2018) - Messaoudi, Hassiba; Thomas, Sébastien; Djaidja, Abdelhamid; Slyemi, Samira; Barama, Akila
Highlights: Preparation and characterization of bulk (Lax NiOy ) and supported (Lax NiOy /MgAl2 O4 ) catalysts with spinel and perovskite structures. Higher specific surfaces area and better nickel dispersion were obtained for the supported catalysts. Good reactivity and stability for the dry reforming of methane were observed for both supported catalysts for 65 h of catalytic reaction. Kinetic modelling shows that water gas shift and dry methane reforming convert same amount of CO2 for temperature over 1023 K . Abstract: Bulk Lax NiOy and supported Lax NiOy /MgAl2 O4 (with x = 1 or 2 and y = 3 or 4) catalysts have been prepared respectively by sol-gel and impregnation methods The elaborated materials have been characterized by XRD, BET, H2 -TPR, H2 -chemisorption and TPO. The catalytic activity was evaluated in dry reforming of methane (DMR) with an equimolar ratio of CH4 and CO2 . XRD analysis shows the presence of LaNiO3, La2 NiO4 and MgAl2 O4 phases. Higher specific surface areas and nickel dispersions were obtained for the supported catalysts. H2 -TPR analysis revealed a low reducibility of the nickel in the supported solids. Supported catalysts were found more active and stable than bulk one in DMR in good agreement with higher Ni dispersion and the beneficial role of the basic support. The XRD analysis performed on the spent catalysts (after 65 h of catalytic test) revealed the presence of the initial phases with metallic nickel species. The TPO analysis showed a low carbon deposition for the supported catalysts. A kinetic study based on the reaction mechanism points out the participation of the reverse water gas shift reaction (RWGS) for the conversion of CO2 and of the produced H2 as well as contribution of steam methane reforming reaction for the conversion of CH4, with water produced from (RWGS), for temperatures over 1023 K.